A Spiritual Theology of Dialogue: Levinas, Burggraeve, and Catholic Theology - Morrison, Glenn (Religions, 2024)
Dialogue needs provocative interlocutors. Instilling a grave and shuddering awakening to the conscience, Emmanuel Levinas has provided a corpus of writings unveiling an immemorial horizon and divine calling of infinite responsibility before the other, the brother/sister stranger. Roger Burggraeve has animated Levinas’ writings within a Christian theological horizon as a source of formation in the service of promoting biblical wisdom and love in the life of faith. The writings of Pope Benedict XVI and Pope Francis together portray a Catholic theological gravity to bring dialogue into a spiritual, practical, and social domain. Accordingly, this article develops the notion of dialogue within a Jewish and Christian lens by introducing the sense of the non-reciprocal character of dialogue, an asymmetrical relation of responsibility to the other evidencing the preconditions of dialogue. Levinas’ notion of non-reciprocal dialogue, taken further by the writings of Burggraeve, reveals a pre-original affectivity or ‘dialogical’ character of interpersonal relations of commitment respecting the other’s mystery and unknowability. This means that the dialogical relation is a pathway of ethical transcendence, a holy ground evoking an integral human ecology of maternity and fraternity. Such covenantal alterity in spiritual theological terms signifies an affectivity of atonement and redemptive love. In this way, the movement towards dialogue reveals a synodal path and holy ground to walk together and imagine an integral ecology of difference and mystery to transform words into sacrifice and truth into redemptive love. Journeying together upon such holy ground witnesses to a spiritual theology of dialogue envisioning a place to hear the “good news” (Lk 4:16) and encounter “the hunger and thirst for righteousness” (Matt 5:6).